Effective Communication of Ukrainian Medical Opinion Leaders in Social Network - Скалацька, Олена Віталіївна; Скалацька, О. В.; Скалацкая, Елена Витальевна; Skalatska, Olena V.; Нерубасська, Алла Олександрівна; Нерубасська, А. О.; Нерубасская, Алла Александровна; Nerubasska, Alla O.; Ямілова, Тетяна Миколаївна; Ямілова, Т. М.; Ямилова, Татьяна Николаевна; Yamilova, Tetiana M.; et al. (Innovare Academics Sciences, 2020)
The article deals with the analysis of effective communication of Ukrainian opinion leaders in social media. In Ukraine, the use of social networking sites Facebook and Instagram has become widespread. There are also two recognized opinion leaders in the field of health care, Yevhen Komarovskiy and Ulana Suprun. Based on a two-step flow model of communication, the authors investigate how opinion leaders create their Internet content on social networks and establish communication with the audience. The study uses qualitative and quantitative research methods, which allow for reproducing the overall scheme of building the opinion leaders' internet content. The features of Ukrainian opinion leaders' effective communication with the audience were determined by specifying content distribution technologies, specifying formats for presenting information as well as identify the subject of messages, selecting out hashtags. According to the results of the study, opinion leaders use different channels of communication with the audience, and patients (own website, a YouTube channel, participation in media projects). Their activities in social networks Instagram and Facebook are confirmed by the regular posting and communication with other users, encouraging feedback. Opinion leaders in the medical field apply the following technologies to create a positive image and maintain credibility among the audience: minimizing messages about private life; creating a column about breaking down health stereotypes; spreading medical innovations; quality visual content; hyperlinks to their other channels; use and creating hashtags; simple and clear advice to their patients.

Стаття присвячена аналізу ефективної комунікації українських лідерів думок у соціальних медіа. В Україні набуло поширення використання соціальних мереж Facebook та Instagram. Також є двоє визнаних лідерів думок у сфері охорони здоров’я – Євген Комаровський та Уляна Супрун. На основі двоетапної моделі комунікації автори досліджують, як лідери думок створюють свій Інтернет-контент у соціальних мережах та налагоджують комунікацію з аудиторією. У дослідженні використовуються якісні та кількісні методи дослідження, що дозволяють відтворити загальну схему побудови інтернет-контенту лідерів думок. Особливості ефективної комунікації українських лідерів думок з аудиторією визначалися шляхом визначення технологій поширення контенту, визначення форматів подання інформації, а також визначення тематики повідомлень, виділення хештегів. За результатами дослідження, лідери думок використовують різні канали комунікації з аудиторією та пацієнтами (власний сайт, YouTube-канал, участь у медіа-проектах). Їхня діяльність у соціальних мережах Instagram та Facebook підтверджується регулярними публікаціями та спілкуванням з іншими користувачами, заохочувальними відгуками. Лідери думок у сфері медицини застосовують такі технології для створення позитивного іміджу та підтримки довіри серед аудиторії: мінімізація повідомлень про особисте життя; створення колонки про руйнування стереотипів здоров’я; поширення медичних інновацій; якісний візуальний контент; гіперпосилання на інші їхні канали; використання та створення хештегів; прості та зрозумілі поради своїм пацієнтам.
Skalatska O. Effective Communication of Ukrainian Medical Opinion Leaders in Social Network / O. Skalatska, A. Nerubasska, T. Yamilova, O. Bielyaieva, L. Zahorodnia // Journal of Critical Reviews. - Vol. 7. - Is. 04. - Innovare Academics Sciences. 2020. - P. 1673-1679.
Keywords: opinion leader; social networks; hashtag; doctor's image; communication; feedback; post; audience; лідер думок; соціальні мережі; хештег; імідж лікаря; комунікація; зворотній зв’язок; пост; аудиторія; Research Subject Categories::SOCIAL SCIENCES::Other social sciences::Media and communication studies